Understanding hydrological cycle dynamics due to changing land use and land cover: Congo Basin study - Batra, N; Yang, Y. C. E.; Choi, H.I.; Kumar, P.; Xueliang Cai; Fraiture, Charlotte de (2008)
Land use and land cover changes (LULCC) significantly modify the hydrological flow regime of the watersheds, affecting water resources and environment from regional to global scale. In recent years, with an increased number of launched satellites, regular updates of land-cover databases are available. This study seeks to advance and integrate water and energy cycle observation, scientific understanding, and its prediction to enable society to cope with future climate adversities due to LULCC. We use the Common Land Model [1] which is developed with enhanced spatial and temporal resolution, physical complexity, hydrologic theory and processes to quantify the impact of LULCC on hydrological cycle dynamics. A consistent global GIS-based dataset is constructed for the surface boundary conditions of the model from existing observational datasets available in various resolutions, map projections and data formats. Incorporation of the projected LULCC of Intergovernmental Panel on Climate Change (IPCC) A1B scenario [2] into our hydrologic model enhances scientific understanding of LULCC impact on the seasonal hydrological dynamics. An interesting case study is addressed over the Congo basin located in the western central Africa which has the second largest rain forest area in the world. It is surrounded by plateaus merging into savannas in the south, mountainous terraces and grassland in the west and mountainous glaciers in the east. Savanna and Evergreen Broadleaf forest are projected to be cleared off in places to be replaced by dryland, cropland and pasture. By 2100, there would be a 10% decrease in savanna and 2% decrease in evergreen forest under A1B scenario of IPCC. Each land cover class has a particular set of characteristics defined in the model and any change in land cover type changes the vegetation properties, rooting depth, roughness length, etc. which results in a change of energy and water fluxes. Deforestation of evergreen forests and intense land clearing of savanna leads to reduction in evapotranspiration. Model results show that the gain in runoff follows the pattern of loss in evapotranspiration.